(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Increasing the level of electoral and legal culture of students. There are the following factors: education, university, media, Internet, authorities, family. In this case, the activity of the university (on the example of the Kazakh National University named after Al-Farabi) is on the interest of authors, as one of the tools for the formation and enhancement of the electoral and legal culture of students – Oralman. The formation of the electoral and legal culture of student youth is an integral component of the higher education system and is based on the awareness of culture as a process of creative and educational activities of the university. It is within the walls of the university and the student environment is formed a significant part of the political and civic socialization of the individual. In this case, the task of the educational system is clear: reaching a level where everyone would respect their rights by virtue of moral beliefs. To date, the university has a wide range of tools and ways to increase the involvement of young people in political processes. The most effective of them: the system of higher education, its social-educational activity and corporate media of the university. Key words: electoral and legal culture, student youth, oralmans.